COVID-19-Considerations for the Female Athlete - Georgie Bruinvels; Georgie Bruinvels; Nathan A. Lewis; Nathan A. Lewis; Richard C. Blagrove; Dawn Scott; Richard J. Simpson; Richard J. Simpson; Richard J. Simpson; Aaron L. Baggish; John P. Rogers; John P. Rogers; et al. (Frontiers Media S.A., 2021)
The SARS CoV-2 virus (COVID-19) caused the whole sporting calendar to be paused. As we embark on the challenge of navigating through the return to play (RTP) process, there is a necessity to consider the needs of all athletes. This commentary specifically considers recommendations and requirements for the female athlete with a physiological emphasis during and following the COVID-19 pandemic, however, it will be relevant for any similar future scenarios that may present. It is important to acknowledge that there remain many unknowns surrounding COVID-19 and the female athlete both in the short- and long-term.